Policy Of Specific Time Working Agreement (Pkwt) On Law Number 11 Of 2020 Concerning Creation Work In Welfare Perspective Social And Subjective - Sutrisno; Imam Budi Santoso; Holyness N. Singadimedja (LEGAL BRIEF, 2021)
There are two types of work agreement issues as regulated in the Manpower Act which qualifies work agreements, namely, a Specific Time Work Agreement (PKWT) and an Indefinite Work Agreement. Specific Time (PKWT) in Law Number 11 of 2020 concerning Job Creation in Social Welfare and Subjective Perspectives. This research was conducted using a normative juridical approach, namely an approach that focuses on research and studies through theories and legal principles, as well as legislation on employment, especially related to non-permanent workers (PKWT) as regulated in the Job Creation Act. the policy of Specific Time Work Agreements (PKWT) in Law Number 11 of 2020 concerning Job Creation in the perspective of social and subjective welfare related to the goals of labor development in Indonesia has not been achieved optimally, because workers still feel they are being treated unfairly. This PKWT status does not provide legal certainty and a sense of security for the right to work guaranteed by the State. This PKWT status if viewed from the aspect of social welfare does not reflect welfare because at any time the entrepreneur can terminate it without any guarantee of welfare for his life and if it occurs as a whole it will lead to poverty and the feasibility of a prosperous life as mandated by the constitution